Calcule o valor numérico da "função do 2 grau" f(X): - 2x* -7X -6 , quando :
a) f(-2):
b) f(2):
chambber:
Seria f(x) = -2x² -7x - 6?
Respostas
respondido por:
3
Para
:
![-2*(-2)^2 - 7*(-2) - 6 = \\ -2 * 4 + 14 - 6 = \\ -8 + 14 - 6 = \\ -14 + 14 = 0 -2*(-2)^2 - 7*(-2) - 6 = \\ -2 * 4 + 14 - 6 = \\ -8 + 14 - 6 = \\ -14 + 14 = 0](https://tex.z-dn.net/?f=-2%2A%28-2%29%5E2+-+7%2A%28-2%29+-+6+%3D+%5C%5C+-2+%2A+4+%2B+14+-+6+%3D+%5C%5C+-8+%2B+14+-+6+%3D+%5C%5C+-14+%2B+14+%3D+0)
Para
:
![-2*(2)^2 - 7*(2) - 6 = \\ -2*4 - 14 - 6 = \\ -8 - 14 - 6 = -28 -2*(2)^2 - 7*(2) - 6 = \\ -2*4 - 14 - 6 = \\ -8 - 14 - 6 = -28](https://tex.z-dn.net/?f=-2%2A%282%29%5E2+-+7%2A%282%29+-+6+%3D+%5C%5C+-2%2A4+-+14+-+6+%3D+%5C%5C+-8+-+14+-+6+%3D+-28)
Portanto:
![f(-2) = 0 f(-2) = 0](https://tex.z-dn.net/?f=f%28-2%29+%3D+0)
![f(2) = -28 f(2) = -28](https://tex.z-dn.net/?f=f%282%29+%3D+-28)
Para
Portanto:
respondido por:
3
a)
f(x) = - 2x² - 7x - 6
f(-2) = - 2.(-2)² - 7.(-2) - 6
f(-2) = - 2.4 + 14 - 6
f(-2) = - 8 + 8
f(-2) = 0
****************************
b)
f(x) = - 2x² - 7x - 6
f(2) = - 2.2² - 7.2 - 6
f(2) = - 2.4 - 14 - 6
f(2) = - 8 - 20
f(2) = - 28
f(x) = - 2x² - 7x - 6
f(-2) = - 2.(-2)² - 7.(-2) - 6
f(-2) = - 2.4 + 14 - 6
f(-2) = - 8 + 8
f(-2) = 0
****************************
b)
f(x) = - 2x² - 7x - 6
f(2) = - 2.2² - 7.2 - 6
f(2) = - 2.4 - 14 - 6
f(2) = - 8 - 20
f(2) = - 28
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás